At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's begin with the task of finding [tex]\( P(-4) \)[/tex] for the polynomial [tex]\( P(x) = 4x^4 - 9x^2 + 8x + 2 \)[/tex] by direct substitution.
### Step-by-Step Solution
Step 1: Understand the polynomial and the value you need to substitute.
- The polynomial given is [tex]\( P(x) = 4x^4 - 9x^2 + 8x + 2 \)[/tex].
- We are asked to find [tex]\( P(-4) \)[/tex], so we will substitute [tex]\( x = -4 \)[/tex] into the polynomial.
Step 2: Substitute [tex]\( x = -4 \)[/tex] into the polynomial.
- Substitute [tex]\( -4 \)[/tex] for [tex]\( x \)[/tex] in each term of the polynomial:
[tex]\[ P(-4) = 4(-4)^4 - 9(-4)^2 + 8(-4) + 2 \][/tex]
Step 3: Compute each term individually.
- Calculate [tex]\((-4)^4 \)[/tex]:
[tex]\[ (-4)^4 = 256 \][/tex]
So, [tex]\( 4 \cdot 256 = 1024 \)[/tex].
- Calculate [tex]\((-4)^2 \)[/tex]:
[tex]\[ (-4)^2 = 16 \][/tex]
So, [tex]\( 9 \cdot 16 = 144 \)[/tex].
- Calculate [tex]\( 8(-4) \)[/tex]:
[tex]\[ 8 \cdot (-4) = -32 \][/tex]
- The constant term in the polynomial is [tex]\( +2 \)[/tex].
Step 4: Combine the computed values.
- Substitute the calculated values back into the polynomial expression:
[tex]\[ P(-4) = 1024 - 144 - 32 + 2 \][/tex]
Step 5: Simplify the expression.
- Perform the arithmetic step-by-step:
[tex]\[ 1024 - 144 = 880 \][/tex]
[tex]\[ 880 - 32 = 848 \][/tex]
[tex]\[ 848 + 2 = 850 \][/tex]
So, [tex]\( P(-4) = 850 \)[/tex].
### Conclusion
Therefore, by direct substitution, [tex]\( P(-4) = 850 \)[/tex].
### Step-by-Step Solution
Step 1: Understand the polynomial and the value you need to substitute.
- The polynomial given is [tex]\( P(x) = 4x^4 - 9x^2 + 8x + 2 \)[/tex].
- We are asked to find [tex]\( P(-4) \)[/tex], so we will substitute [tex]\( x = -4 \)[/tex] into the polynomial.
Step 2: Substitute [tex]\( x = -4 \)[/tex] into the polynomial.
- Substitute [tex]\( -4 \)[/tex] for [tex]\( x \)[/tex] in each term of the polynomial:
[tex]\[ P(-4) = 4(-4)^4 - 9(-4)^2 + 8(-4) + 2 \][/tex]
Step 3: Compute each term individually.
- Calculate [tex]\((-4)^4 \)[/tex]:
[tex]\[ (-4)^4 = 256 \][/tex]
So, [tex]\( 4 \cdot 256 = 1024 \)[/tex].
- Calculate [tex]\((-4)^2 \)[/tex]:
[tex]\[ (-4)^2 = 16 \][/tex]
So, [tex]\( 9 \cdot 16 = 144 \)[/tex].
- Calculate [tex]\( 8(-4) \)[/tex]:
[tex]\[ 8 \cdot (-4) = -32 \][/tex]
- The constant term in the polynomial is [tex]\( +2 \)[/tex].
Step 4: Combine the computed values.
- Substitute the calculated values back into the polynomial expression:
[tex]\[ P(-4) = 1024 - 144 - 32 + 2 \][/tex]
Step 5: Simplify the expression.
- Perform the arithmetic step-by-step:
[tex]\[ 1024 - 144 = 880 \][/tex]
[tex]\[ 880 - 32 = 848 \][/tex]
[tex]\[ 848 + 2 = 850 \][/tex]
So, [tex]\( P(-4) = 850 \)[/tex].
### Conclusion
Therefore, by direct substitution, [tex]\( P(-4) = 850 \)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.